2020
DOI: 10.1016/j.ymthe.2020.04.017
|View full text |Cite
|
Sign up to set email alerts
|

AAV-CRISPR Gene Editing Is Negated by Pre-existing Immunity to Cas9

Abstract: Adeno-associated viral (AAV) vectors are a leading candidate for the delivery of CRISPR-Cas9 for therapeutic genome editing in vivo . However, AAV-based delivery involves persistent expression of the Cas9 nuclease, a bacterial protein. Recent studies indicate a high prevalence of neutralizing antibodies and T cells specific to the commonly used Cas9 orthologs from Streptococcus pyogenes (SpCas9) and Staphylococcus aureus (SaCas9) in humans. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 37 publications
3
92
1
Order By: Relevance
“…An additional barrier for the therapeutic application of CRISPR-Cas is the substantial prevalence of pre-existing Cas9 immunity in the human population, with up to 78% of individuals having anti-Cas9 IgG antibodies and Cas9-specific T cells [ 238 , 239 ]. In the study by Li et al, AAV containing CRISPR-Cas9 introduced into a host with pre-existing immunity led to cytotoxic T cell responses and elimination of gene-modified target cells in vivo [ 55 ], providing evidence that Cas9 immunity cannot be circumvented by AAVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional barrier for the therapeutic application of CRISPR-Cas is the substantial prevalence of pre-existing Cas9 immunity in the human population, with up to 78% of individuals having anti-Cas9 IgG antibodies and Cas9-specific T cells [ 238 , 239 ]. In the study by Li et al, AAV containing CRISPR-Cas9 introduced into a host with pre-existing immunity led to cytotoxic T cell responses and elimination of gene-modified target cells in vivo [ 55 ], providing evidence that Cas9 immunity cannot be circumvented by AAVs.…”
Section: Resultsmentioning
confidence: 99%
“…The CRISPR-Cas9 from Staphylococcus aureus (SaCas9) uses an sgRNA to bind to sites upstream of a 5′-NNGRRT PAM sequence. The SaCas9 has been employed in preclinical studies using animal models of human diseases that demonstrated successful therapeutic application [ 55 , 56 ]. In addition, SaCas9 reagents, similar to other Cas homologs, are commercially available to enable ease of their direct delivery as preformed sgRNA-Cas9 RNPs for potent cleavage activity at endogenous sites in cells.…”
Section: Gene-editing Toolsmentioning
confidence: 99%
“…First, an immune response to the editor, delivery vector, or the edited protein product is possible. Continuous constitutive expression of SauCas9 in hepatocytes elicits an innate immune response, which accelerates the death of the edited hepatocytes 94 . Using strategies with a shorter-term expression of genome editor (mRNA, or RNP) may prevent adverse events in the edited cells.…”
Section: Discussionmentioning
confidence: 99%
“…198 Another study showed that prestimulated anti-Cas9 cytotoxic T cells completely negated the therapeutic effect of Cas9 gene editing within 12 weeks. 203 Although no human studies have shown an inhibitory effect of the immune system as yet, Cas9-reactive T cells clearly exist in significant fractions of the population. 199,201 The interaction of the immune system with CRISPR-based therapies needs further study, but preliminary data suggest that it could become an obstacle to in vivo CRISPR-Cas therapies.…”
Section: Administrationmentioning
confidence: 99%